Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

TDOF PID Controller for Enhanced Disturbance Rejection with MS-Constraints for Speed Control of Marine Diesel Engine - Gun-Baek So; Gang-Gyoo Jin; Chan-Ha Lee; Hye-Rim So; Dae-Jeong Kim; Jong-Kap Ahn (Journal of Marine Science and Engineering, 2024)
This study proposes a two-degree-of-freedom PID controller design and tuning method based on a simple pole placement approach to enhance servo and regulatory performance while ensuring the stability of diesel engines. In the modeling of the control target, the actuator is analytically modeled. In contrast, the type of model for the diesel engine is derived analytically, and its parameter estimation uses operational data from naval ships. The proposed controller consists of a PID controller to improve regulatory performance and a set-point filter to enhance servo response. PID controller parameters consist of the parameters of the controlled plant model and a single tuning variable. At the same time, the set-point filter comprises the controller parameters and a single weighting factor. To ensure the robust stability of the controller, the controller parameters are tuned based on the maximum sensitivity. To verify the effectiveness of this study, simulations for the speed control of a diesel engine with inherent nonlinearity were conducted under three scenarios. Performance was quantitatively analyzed using the integral of time-weighted absolute error, 2% settling time, 2% recovery time, specified maximum sensitivity, and maximum peak response value, and was compared with Skogestad’s IMC and Lee’s IMC. Based on evaluation indices, the proposed controller demonstrated superior performance in both servo and regulatory responses compared to the two existing control techniques while ensuring stability.

Establishment of embryogenic cultures and determination of their bioactive properties in Rosa rugosa - Hye-Rim Jang; Hyun-Jeong Lee; Byung-Jun Park; Ok-Ja Pee; Kee-Yoeup Paek; So-Young Park (Horticulture, Environment, and Biotechnology, 2016)

Diagnostic usefulness of the GenoType MTBDR plus assay for detecting drug-resistant tuberculosis using AFB smear-negative specimens with positive TB-PCR result - Young Seok Lee; Hye-Rim Kang; Si-Hyeong Lee; Yunmi Kim; Mi-Yeong Kim; Jeong Hwan Shin; Jae Young Moon; Hyun-Kyung Lee; So Young Park; Eun-Kyung Mo; Yong Bum Park; Soo-Yoon Moon; et al. (Infectious Diseases, 2016)